EDUKASI TERKAIT FAKTOR YANG MEMPENGARUHI TIMBULNYA NYERI PUNGGUNG BAWAH PADA KARYAWAN WORK FROM HOME DIMASA PANDEMI COVID-19 - Siti Sarah Bintang Sarah Bintang; Isidorus Jehaman; Sabirin Berampu; Akhsan .; Miftahul Zannah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Work form home (WFH) has the potential to cause musculoskeletal disorders. Musculoskeletal disorders characterized by generalized chronic pain. Based on epidemiological studies and occupational factors can increase the risk of musculoskeletal disorders. The implementation of PkM activities for private employees who are carrying out Work From Home, is carried out through notifications via the internet by filling out a google form with a sample of 30 workers who are at home (work from home) during the COVID 19 pandemic. The results show that the distribution of back pain frequency lower in employees showed a mild pain rate of 58% and moderate pain of 41.9%. There is an increase in knowledge regarding the factors that influence the occurrence of lower back pain in employees working from home during the Covid-19 pandemic